Use and perception of open source by students of the national university in non IT careers - Gómez Fernández, Carolina (2019)
This paper discloses some initiatives that have been carried out by the National University with open source and an exploratory study of the use and perception of a part of the students of the National University that are studying careers different from those of IT technologies, with In order to know the level of knowledge of free software. © 2019 IEEE.